Herding behavior in Ramadan and financial crises: The case of the Pakistani stock market - Imran Yousaf; Shoaib Ali; Syed Zulfiqar Ali Shah (Financial Innovation, 2018)
This study examines herding behavior in the Pakistani Stock Market under different market conditions, focusing on the Ramadan effect and Crisis period by using data from 2004 to 2014. Two regression models of Christie and Huang (Financ Analysts J 51:31-37, 1995) and Chang et al., (J Bank Finance 24:1651-1679, 2000) are used for herding estimations. Results based on daily stock data reveal that there is an absence of herding behavior during rising (up) and falling (down) market as well as during high and low volatility in market. While herding behavior is detected during low trading volume days. Yearly analysis shows that herding existed during 2005, 2006 and 2007, while it is not evident during rest of the period. However, herding behavior is not detected during Ramadan. Furthermore, during financial crisis of 2007-08, Pakistani Stock Market exhibits herding behavior due to higher uncertainty and information asymmetry.
Keywords: 650; Herding behavior; Financial crisis; Ramadan effect; Stock markets